Lithuanian Scientific Medical Periodicals in the Third-Fifth Decade of the 20th Century (till 1944) - Silvija Stakulienė (Knygotyra)
The aim of this article - to overview two scientific medical periodical publications "Medicina" (Medicine) and "Vytauto Didžiojo universiteto Medicinos fakulteto darbai" (Scientific Works of the Medical Faculty of Vytautas Magnus). They were begun to be published in Lithuania only after having regained the freedom of the press. Research period covers the years 1920-1944. The author analyzes their origin, publishing process and consistency of evolution. It is still not well enough investigated subject in the history of Lithuanian medicine and press.